Facile Electrodeposition and Aging to Generate 3-Dimensional α-MnO2 Battery Cathodes. Issue 10 (1st October 2022) - Campos, Armando Rodriguez; Vila, Mallory N.; Haddad, Milan; Housel, Lisa M.; Takeuchi, Esther; Marschilok, Amy; Takeuchi, Kenneth; Poyraz, Altug S.
Abstract : Conventional tape casting forms 2-dimensional (2D) electrodes containing active material, conductive additive, and binder with restricted ion access as electrodes increase in thickness. To improve the transport properties, 3D architectures were developed using electrodeposition to ensure contact between the active material with the substrate, and provide enhanced electrolyte access. This paper investigates electrodeposition of cryptomelane ( α -MnO2 ) as a model cathode material to efficiently accommodate (de)lithation and increase areal capacity vs conventional 2D coatings. Electodeposited samples on titantium (Ti) foil substrates were characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM) and show a linear increase of the average oxidation of Mn (3.5–3.8) and active mass loading (1.27–9.9 mg) with deposition and aging times (0–120 min). The initial deposition is amorphous and forms the crystalline material during the elevated temperature aging step. The active material, α -MnO2, was also deposited on C-cloth and these cathodes at deposition times of 3, 6, and 9 min deliver 9, 36, and 69% higher areal capacities, respectively, at 0.2 mA cm −2 compared to conventional 2D electrodes with a mass loading equal to the 3 min sample. These results demonstrate the benefit of α -MnO2 within a porous architecture providing enhanced transport properties.